Syn-tectonic sulphide remobilization and trace element redistribution at the Falun pyritic Zn-Pb-Cu-(Au-Ag) sulphide deposit, Bergslagen, Sweden - Kampmann, Tobias Christoph; Jansson, Nils F.; Stephens, Michael B.; Olin, Paul H.; Gilbert, Sarah; Wanhainen, Christina (Ore Geology Reviews, 2018)
Mineralization types at the Palaeoproterozoic Falun base metal sulphide deposit are predominantly pyritic Zn-Pb-Cu-rich massive sulphide mineralization, disseminated to semi-massive Cu-Au mineralization, auriferous quartz veins, and mineralized shear zones of talc-chlorite-dominated schist. The massive and disseminated to semi-massive sulphide mineralization types were subject to polyphase ductile deformation (D1 and D2) and metamorphism under low-P, lower-amphibolite facies conditions, which led to the development of ore textures and paragenetic relationships indicating both mechanical and chemical remobilization of sulphides. In the massive sulphide mineralization, rare inclusion-rich pyrite occurs as relic cores inside inclusion-poor metamorphosed pyrite. Imaging and spot analysis using multielement laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) reveal that inclusion-poor pyrite was depleted in trace elements, which were originally present as non-stoichiometric lattice substitutions or in mineral inclusions. The inclusion-rich pyrite was shielded from depletion and, at least partly, retained its initially higher trace element concentrations, including Au. Gold is also associated with chalcopyrite in the disseminated to semi-massive Cu-Au mineralization and in the system of auriferous quartz veins hosted therein, the latter being also affected by the D2 ductile strain. It is inferred that emplacement of the vein system took place after the peak of metamorphism, which occurred between D1 and D2, but prior to and possibly even shortly after completion of the D2 deformational event. Similarities in trace element signatures in chalcopyrite are compatible with the interpretation that the quartz veins formed by local chemical remobilization of components from the Cu-Au mineralization. Transport of liberated Au from pyrite during grain growth in the massive sulphide mineralization may have upgraded the Au endowment in the quartz veins, leading to the additional formation of native gold in the ...